Eliciting cytotoxic T-lymphocyte responses from synthetic vectors containing one or two epitopes in a C57BL/6 mouse model using peptide-containing biodegradable microspheres and adjuvants - Rubsamen, R. M.; Herst, C. V.; Lloyd, P. M.; Heckerman, David (2014)
We describe a vaccine delivery mechanism consisting of a synthetic, non-living vector of large d,l poly(lactic-co-glycolic) acid (PLGA) microspheres that carry specific cytotoxic T lymphocyte (CTL) epitopes. We demonstrate in mice that it can be used to elicit substantial interferon gamma ELISPOT responses to more than one specific epitope in the same individual. Our data suggest that a superior adjuvant configuration for the formulation is to place a TLR-9 agonist CpG inside the microsphere and a TLR-4 agonist MPLA in the injectate solution. This finding contrasts with the observations of others. Our approach provides a means to elicit immune responses efficiently to select epitopes, which may be important for an effective vaccine against HIV.